THE ROLE OF SOCIALIZATION IN FORMING SUSTAINABLE CONSUMPTION BEHAVIOR IN SCHOOL-AGE CHILDREN: Peran Sosialisasi dalam Pembentukan Perilaku Konsumsi Berkelanjutan pada Anak Usia Sekolah - Andini, Putri Fildzah; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2024)
Sustainable consumption behavior, namely making decisions that ensure the environment will not be damaged by SDG’s goal 12. This research explores the relationship between respondent characteristics and sustainable consumption behavior and the influence of teacher socialization, parental socialization, and social media on consumption and sustainability values. This research was conducted cross-sectionally on 218 elementary school students using cluster random sampling. The data was processed using SPSS 25 and Smart-PLS 3. The results showed that sustainable consumption behavior among male students tended to be better and also tended to be better among children who had working mothers. The results of the SEM analysis showed a significant influence of parental socialization on sustainable consumption behavior. In addition, a significant positive indirect effect was found between teacher socialization, parental socialization, and social media exposure on sustainable consumption behavior through consumption values. Therefore, parents need to provide positive socialization to children regarding consumption values to encourage sustainable consumption behavior in children.